Close enough to hear God breathe : the great story of divine intimacy - Paul, Greg, 1958- (Nashville, Tenn. : Thomas Nelson, 2011)
In Close Enough to Hear God Breathe, readers encounter a rich message that recounts the story of a God who has been inviting all of humanity, and each individual, into his tender embrace since time began. --from publisher descriptioin
The voice from above -- The heart of the matter -- The great story -- A good likeness -- Happiness is a hot shower -- Hammer and nails -- The beauty of a broken mirror -- Dreaming of me -- Chocolate and rosebuds -- Striking off the chains -- Traveling to Canaan -- Plastic pop bottles -- Aboard the Amadeus -- Erotica -- Dancing in the new world.
Keywords: Spiritual life -- Christianity